The importance of lining the irrigation networks in the district of independence (Journal of the College of Basic Education, 2022)
The research aims to study the integrated aspects of the subject of lining the irrigation channels in the Rashidiya district of Istiqlal, in order to increase the need for water in quantity and quality. Therefore, the irrigation network must be able to deliver the quantities of water required for these crops. It also requires that the irrigation network be developed. The type of liner in the study area is concrete lining, which contributed to the reduction of post-construction costs and increased water flow velocity, resulting in less water loss. It also contributes to reducing the problems of agricultural land adjacent to these channels.